Sensitivity of an organisation as a condition for the implementation of an idea of the common good in the sphere of human capital management (Economic and Political Thought, 2014)
The article lets its readers get acquainted with some theoretical issues.It aims to systemise the knowledge of an organisation’s sensitivity from aninterdisciplinary perspective and present the authors’ proposal for instrumentsmeasuring an organisation’s sensitivity towards its employees. Making useof the output of psychology, the authors introduce the categorization intosensory, emotional and social sensitivity of organisations. Within each ofthem, they indicate specific activities that, on the one hand can be a prooffor the existence of one type of sensitivity, and on the other hand a hint forthe management staff as to how to build and/or strengthen an organisation’ssensitivity. They show that an organisation’s sensitivity is necessary and it laysa foundation for the implementation of the idea of the common good.